Determination Of Total Flavonoid Content Of Bajakah Tampala And Kalalawit Roots Using The Reflux - Sasi Yuni Kirana; Rizki Febrianti; Wilda Amananti (Universitas Negeri Medan, 2023)
Bajakah is one of the plants found in the forest around Muara Badak. Bajakah root contains flavonoids which have potential as natural ingredients that have medicinal properties. Currently, there are two types of bajakah root on the market, namely tampala and kalalawit. This study aims to determine the content and total flavonoid content of the extract of the Bajakah root from the two types of Bajakah root. The research procedure was initiated by the process of extracting the roots of the Bajakah root using the reflux method using 96% ethanol. The reflux extraction results are then carried out by an evaporation process to obtain a thick extract. The second step is to test the flavone content through a color test. And the quantitative test for determining total flavonoid levels was carried out by UV-Vis Spectrophotometry. Based on the results of a qualitative test using a color reaction, it shows that the roots of the kalalawit and tampala bajakar contain flavonoids. Where the total flavonoid content in the roots of Bajakah Tampala was 59.38% and in Bajakah Kalalawi roots was 47.14%.